Effects of introducing a fee for inpatient overstays on the rate of death and readmissions across municipalities in Norway. (June 2019) - Ambugo, Eliva Atieno; Hagen, Terje P.
Abstract: The Norwegian healthcare coordination reform (Samhandlingsreformen) was implemented from January 1, 2012. In addition to providing municipalities with funding to strengthen their health infrastructure, it required municipalities to pay hospitals a daily fee for patients who, having been declared ready for discharge and in need of municipal health services, were not received by the municipalities on time. This study examines the effects of the reform on the rate of death and readmissions occurring within 60 days of hospitalization. We use aggregated municipal data for years 2009, 2010, 2012–2014 (N = 1646) for Norwegian patients (age 18+) hospitalized in the same years for COPD/asthma, heart failure, hip fracture, and stroke. We stratify our analyses of the municipal data by these patient groups. Our linear regression models test for moderated (interaction) effects whereby associations between the reform and the rate of death and readmissions vary by whether or not patients were classified as ready for discharge and in need of follow-up care in the municipality. The models adjust for municipal sociodemographic and health characteristics. We found no statistically significant moderated effects of the reform across the patient groups, except for patients with stroke (b = .027, SE = 0.109, p < .05). Specifically, compared to the pre-reform period (2009–2010), the post-reform period (2012–2014) was associated with a higher rate of readmissions at high predicted values of needing follow-up care. Even though our analyses of municipal data suggest that patients with stroke are vulnerable to the reform and its incentive scheme, there is no strong evidence overall to suggest that the Norwegian healthcare coordination reform is functioning in a manner that exacerbates the risk of death and readmissions. Highlights: Reform aimed at fewer inpatient overstays and more post-discharge community care. Overall, the reform is not significantly linked to increased risk of adverse events. Patients with stroke appear vulnerable to the reform.